2016
DOI: 10.1371/journal.pone.0165831
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Effects of Glycyrrhetinic Acid and Its Derivatives on Staphylococcus aureus

Abstract: Staphylococcus aureus is a major pathogen in humans and causes serious problems due to antibiotic resistance. We investigated the antimicrobial effect of glycyrrhetinic acid (GRA) and its derivatives against 50 clinical S. aureus strains, including 18 methicillin-resistant strains. The minimum inhibitory concentrations (MICs) of GRA, dipotassium glycyrrhizate, disodium succinoyl glycyrrhetinate (GR-SU), stearyl glycyrrhetinate and glycyrrhetinyl stearate were evaluated against various S. aureus strains. Additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 37 publications
2
39
0
Order By: Relevance
“…This hypothesis is consistent with our previous findings concerning S. aureus . Comprehensive analysis of gene expression in S. aureus by DNA microarray analysis showed that GR‐SU treatment alters expression of many genes related to sugar metabolism . Additionally, the minimum concentrations of glucose for growth of S .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This hypothesis is consistent with our previous findings concerning S. aureus . Comprehensive analysis of gene expression in S. aureus by DNA microarray analysis showed that GR‐SU treatment alters expression of many genes related to sugar metabolism . Additionally, the minimum concentrations of glucose for growth of S .…”
Section: Discussionmentioning
confidence: 99%
“…GRA is a major component of licorice extract, which is derived from Leguminosae perennials found in the Mediterranean region, South Russia, central Asia, northern China, and America. GR‐SU, a derivative of GRA, is formed by adding a succinic acid moiety to increase water solubility . GRA has been reported to exhibit anti‐inflammatory, antiallergic, and antipeptic ulcer properties, among others .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, GA and its derivative, disodium 3‐succinyloxy β‐glycyrrhetinate, improved the action of gentamicin against clinical S. aureus strains. No such effect was observed for the combination of GA with chloramphenicol, ofloxacin or erythromycin . GA and its 30‐piperazine analogue also displayed a synergistic effect when combined with the first‐line anti‐tuberculous drugs isoniazid, rifampicin and streptomycin; they also significantly reduced the MIC values of these drugs against drug‐resistant Mycobacterium bovis .…”
Section: Antimicrobial Activity Of Gamentioning
confidence: 99%